Strategi Penurunan Pengangguran di Indonesia Tinjauan Kebijakan dan Implementasi - liasari, nancy herninda (Maliki Interdisciplinary Journal, 2024)
This study analyses various efforts that have been and are being made by the Indonesian government to reduce unemployment. Through an in-depth look at related policies, regulations and programs, this study identifies strengths, weaknesses and gaps in the implementation of these policies. To examine the effectiveness of policies in creating new jobs, improving the quality of the workforce, and reducing the overall unemployment rate. This provides an overview of strstegies for reducing unemployment in Indonesia, through literature studies and quantitative and qualitative data analysis, it can identify factors that influence the unemployment rate and evaluate various policies that have been implemented. In addition, it proposes more sustainable policy recommendations to overcome the problem of unemployment in Indonesia by considering appropriate economic, social and demographic conditions. Unemployment is one of the complex problems faced by Indonesia, in overcoming this problem, several strategies are needed that are sustainable and can be considered, such as improving the quality of human resources, creating new jobs, and overcoming existing challenges. Apart from that, it is also important to continue to evaluate and adaptto changing economic and social conditions.